Effects of herbal medicines (Eunkyosan/Yin qiao san and Samsoeum/Shen su yin) for treating the common cold: A randomized, placebo-controlled, multicenter clinical trial - Kwan-Il Kim; Minna Hong; Yang-Chun Park; Beom-Joon Lee; Kitae Kim; Byoung Kab Kang; Jun-Yong Choi (Integrative Medicine Research)
Background: Eunkyosan (EKS) and Samsoeum (SSE), which are called Yin qiao san and Shen su yin in Chinese, are commonly used herbal medicines for the common cold in East Asian countries. This study aimed to evaluate the effectiveness and safety of EKS and SSE for treating the common cold. Methods: A randomized, patient-assessor-blind, placebo-controlled, parallel, and multicenter clinical trial was conducted. Adult participants who had one or more cold within 48 h before screening, were randomly allocated to EKS, SSE, or placebo groups. The recruitment goal was planned to be 375 participants. They took an EKS, SSE, or placebo, thrice daily for up to 8 days. The primary outcome was the change in the total score of the Wisconsin Upper Respiratory Symptom Scale-21-Korean version (WURSS-21-K) on day 6 compared to the baseline. The secondary outcomes included visual analog scale (VAS) scores and the duration of symptoms was assessed throughout the trial. Results: A total of 128 participants were enrolled and 44, 42, and 42 were allocated to the EKS, SSE, and placebo groups, respectively. This study was prematurely terminated due to the COVID-19 pandemic, and we were unable to recruit all the planned participants (n = 375). EKS showed significant clinical effectiveness over the placebo group in the treatment of the common cold, as assessed by the total, symptom, and quality of life scores of WURSS-21-K and VAS, whereas SSE showed significant improvement over the placebo group in terms of WURSS-21-K symptom score. No severe adverse events were reported. Conclusions: Although EKS and SSE demonstrated statistically significant clinical effectiveness and safety in patients with the common cold, we failed to recruit our pre-planned number of participants. Future definitive full-scale studies are needed to confirm these results. Trial registration: ClinicalTrials. gov, registration number: NCT04073511. Registered on 29 August 2019.